The Erotylidae and Endomychidae (Coleoptera: Cucujoidea) of the Maritime Provinces of Canada: New records, zoogeography, and observations on beetle-fungi relationships and forest health - Majka, Christopher G. (Zootaxa, 2007)
The Erotylidae and Endomychidae of the Maritime Provinces are surveyed. Fifteen species are now known from the region, fourteen in Nova Scotia, seven in New Brunswick, and four on Prince Edward Island. Thirteen new provincial records (seven from Nova Scotia, three from New Brunswick, and three from Prince Edward Island) are reported. Four erotylids, Dacne quadrimaculata (Say), Triplax dissimulator (Crotch), Triplax flavicollis Lacordaire, Triplax macra LeConte; and two endomychids, Rhanidea unicolor (Ziegler) and Lycoperdina ferruginea LeConte, are newly recorded in the Maritime Provinces as a whole. New records of the rare endomychid, Hadromychus chandleri Bousquet & Leschen, are reported. The fauna is examined in a regional zoogeographic context, paying particular attention to the insular faunas of Cape Breton and Prince Edward Islands. Attention is also drawn to the number of species that have been very rarely collected. This apparent scarcity may be related to the long history of forest management in the region, in particular the effects of intensive forestry on the communities of forest fungi on which these species feed and depend. Attention is drawn to the importance of ongoing research to monitor their populations and assess how these species may be employed as indicators of the overall health forest ecosystems.